The Effectiveness of Pulsed Electrical Stimulation in the Management of Osteoarthritis of the Knee: Results of a Double-Blind, Randomised, Placebo-Controlled Repeated-Measures Trial - Fary, Robyn; Carroll, G.; Briffa, T.; Briffa, Kathy (Wiley, 2011)
Objective: To determine the effectiveness of subsensory, pulsed electrical stimulation (PES) in the symptomatic management of osteoarthritis (OA) of the knee. Methods: This was a double-blind, randomized, placebo-controlled, repeated-measures trial in 70 participants with clinical and radiographically diagnosed OA of the knee who were randomized to either PES or placebo. The primary outcome was change in pain score over 26 weeks measured on a 100-mm visual analog scale (VAS). Other measures included pain on the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), function on the WOMAC, patient's global assessment of disease activity (on a 100-mm VAS), joint stiffness on the WOMAC, quality of life on the Medical Outcomes Study Short-Form 36 (SF-36) health survey, physical activity (using the Human Activity Profile and an accelerometer), and global perceived effect (on an 11-point scale). Results: Thirty-four participants were randomized to PES and 36 to placebo. Intent-to-treat analysis showed a statistically significant improvement in VAS pain score over 26 weeks in both groups, but no difference between groups (mean change difference 0.9 mm [95% confidence interval −11.7, 13.4]). Similarly, there were no differences between groups for changes in WOMAC pain, function, and stiffness scores (−5.6 [95% confidence interval −14.9, 3.6], −1.9 [95% confidence interval −9.7, 5.9], and 3.7 [95% confidence interval −6.0, 13.5], respectively), SF-36 physical and mental component summary scores (1.7 [95% confidence interval −1.5, 4.8] and 1.2 [95% confidence interval −2.9, 5.4], respectively), patient's global assessment of disease activity (−2.8 [95% confidence interval −13.9, 8.4]), or activity measures. Fifty-six percent of the PES-treated group achieved a clinically relevant 20-mm improvement in VAS pain score at 26 weeks compared with 44% of controls (12% [95% confidence interval −11%, 33%]). Conclusion: In this sample of subjects with mild-to-moderate symptoms and moderate-to-severe radiographic OA of the knee, 26 weeks of PES was no more effective than placebo.